The Status of Lead and Cadmium in Supplementary Mineral Feed Source of Livestock in Ethiopia (Global Journal of Science Frontier Research, 2016)
In Ethiopia, feed industries are widely using limestone as a cheap source of Ca without adequate information on the bioavailability of its Ca content and the presence of other toxic minerals. This being the case, the present study was conducted to determine the Lead and Cadmium content of samples of limestone, Gypsum and marble powder collected from different parts of Ethiopia. Adequate quantities of lime stone, marble powder and gypsum were procured from different parts of Ethiopia and subjected to laboratory chemical analysis in triplicate. The results of this study clearly showed that the total ash content of all the materials analyzed in this study ranged between 81 and 99%, indicating the potential use of these materials (limestone, marble powder and gypsum) collected from different part of Ethiopia as supplementary mineral feed source in very small amounts. In present work the Pb content (ppm) in Calcium-carbonate and Calcite powder previous work was(123.1± 0.06) and (65.84 ±10.87) respectively while Pb content in the present tested materials(limestone/Calcium-carbonate, marble powder, gypsum) was 24.6, 26.5 and 45.83 respectively. The two samples limestone and marble powder showed almost equal content of Pb while gypsum containing almost double of the two samples.
Keywords: gypsum powder; lime stone; livestock; marble powder; minerals